2019
DOI: 10.1002/chem.201903573
|View full text |Cite
|
Sign up to set email alerts
|

Triplet‐Induced Lesion Formation at CpT and TpC Sites in DNA

Abstract: UV irradiation induces DNA lesions particularly at dipyrimidine sites. Using time‐resolved UV pump (250 nm) and mid‐IR probe spectroscopy the triplet pathway of cyclobutane pyrimidine dimer (CPD) formation within TpC and CpT sequences was studied. The triplet state is initially localized at the thymine base but decays with 30 ns under formation of a biradical state extending over both bases of the dipyrimidine. Subsequently this state either decays back to the electronic ground state on the 100 ns time scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 65 publications
1
16
1
Order By: Relevance
“…Although a triplet manifold has been examined in thymine‐thymine dimers before, this is the first time a detailed QM/MM study explores the formation of CPD in thymine‐cytosine and thymine‐5‐methylcytosine. The work also demonstrates that ISC in thymine rather than other pyrimidine bases is the first step for this mechanism, in agreement with recent experimental findings [11] …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Although a triplet manifold has been examined in thymine‐thymine dimers before, this is the first time a detailed QM/MM study explores the formation of CPD in thymine‐cytosine and thymine‐5‐methylcytosine. The work also demonstrates that ISC in thymine rather than other pyrimidine bases is the first step for this mechanism, in agreement with recent experimental findings [11] …”
Section: Resultssupporting
confidence: 91%
“…To examine the enhanced CPD forming pathway initiated from thymine ππ*, we examine the case for TmCG first and the case for TCG later, when the feasibility of the former is confirmed (right panels in Figure 1). As the results from time‐resolved spectroscopy showed that triplet‐induced CPD formation starts from the localization of the triplet state in the thymine base, [11] we examined the decay pathway starting from thymine ππ* excitation in TmCG here. However, to be thorough, we have also examined the pathway starting from excitation in 5mC (left panel in Figure 1) and this is discussed in the Supporting Information, where it is demonstrated that the pathway is not feasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to direct formation of CPDs by UV irradiation, the relative yield of TT versus C-containing CPDs formed by photosensitization with acetone (≤79%) and NFX (>90%) was much higher than that for NB UVB (31%), and consistent with previous studies with sensitizers ( 41 , 53 , 56 ). The low fraction of C-containing CPDs has traditionally been explained by the fact that T has a lower triplet energy than C, and that triplet states will either preferentially form at, or migrate to, a T. This difference alone, however, would not readily explain why CPDs can’t also form at TC and CT sites which also contain a T. Recent time-resolved studies of CPD formation upon triplet sensitization of T in TT, TC and CT found that the quantum yield is 2–3 less for TC and CT formation than for TT formation, presumably reflecting the relative stability of the biradical intermediates (Figure 2B ) ( 51 ). While this would explain why TT CPDs are formed in higher yield than TC and CT CPDs, it does not explain why the TT/(TC + CT) ratio depends on the triplet energy of the sensitizer, unless the reaction can also proceed through the triplet state of C. Acetone has a triplet state energy of ≈340 kJ/mol ( 52 ) that is higher than that for both T and C, whereas NFX has a much lower energy triplet of ≈270 kJ/mol that can only sensitize T ( 46 , 49 ).…”
Section: Discussionmentioning
confidence: 98%
“…A triplet excited pyrimidine can then form a single bond from C6 to C6 of the adjacent pyrimidine leading to a triplet biradical intermediate ( 3 BR). The triplet biradical can then intersystem cross to the singlet state ( 1 BR) and either go on to the CPD or reverse back to the original dipyrimidine ( 50 , 51 ).…”
Section: Introductionmentioning
confidence: 99%